Characterization of human urinary metabolites of the antimalarial piperaquine. - Tarning, J; Bergqvist, Y; Day, N; Bergquist, J; Arvidsson, B; White, N; Ashton, M; Lindegårdh, N (2006)
Five metabolites of the antimalarial piperaquine (PQ) (1,3-bis-[4-(7-chloroquinolyl-4)-piperazinyl-1]-propane) have been identified and their molecular structures characterized. After a p.o. dose of dihydroartemisinin-piperaquine, urine collected over 16 h from two healthy subjects was analyzed using liquid chromatography (LC)/UV, LC/tandem mass spectrometry (MS/MS), Fourier transform ion cyclotron resonance (FTICR)/MS, and H NMR. Five different peaks were recognized as possible metabolites [M1, 320 m/z; M2, M3, and M4, 551 m/z (PQ + 16 m/z); and M5, 567 m/z (PQ + 32 m/z)] using LC/MS/MS with gradient elution. The proposed carboxylic M1 has a theoretical monoisotopic molecular mass of 320.1166 m/z, which is in accordance with the FTICR/MS (320.1168 m/z) findings. The LC/MS/MS results also showed a 551 m/z metabolite (M2) with a distinct difference both in polarity and fragmentation pattern compared with PQ, 7-hydroxypiperaquine, and the other 551 m/z metabolites. We suggest that this is caused by N-oxidation of PQ. The results showed two metabolites (M3 and M4) with a molecular ion at 551 m/z and similar fragmentation pattern as both PQ and 7-hydroxypiperaquine; therefore, they are likely to be hydroxylated PQ metabolites. The molecular structures of M1 and M2 were also confirmed using H NMR. Urinary excretion rate in one subject suggested a terminal elimination half-life of about 53 days for M1. Assuming formation rate-limiting kinetics, this would support recent findings that the terminal elimination half-life of PQ has been underestimated previously.